Aqueous phase preparation method of chiral iron oxide nanoparticles

By using FeCl3·6H2O and FeCl2·4H2O in the aqueous phase, chiral iron oxide nanoparticles are generated, which solves the problem of complex preparation of chiral iron oxide nanoparticles and insufficient biocompatibility in the prior art, and realizes the problem of the incompatibility of chiral iron oxide nanoparticles. Iron oxide nanoparticles with simple and low-cost large-scale preparation and significant chiral optical signals are used.

CN119191364APending Publication Date: 2024-12-27NANJING MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518667.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing preparation methods for chiral iron oxide nanoparticles have problems such as complex operation, high cost and insufficient biocompatibility, especially in the aqueous phase, which is difficult to achieve simple and low-cost large-scale preparation.

Method used

FeCl3·6H2O and FeCl2·4H2O are used to mix uniformly in ultrapure water, tartaric acid is added as chiral ligand, oxygen is removed by nitrogen bubble, concentrated ammonia water is added to form a second mixed solution, and reaction is carried out under nitrogen protection to form chiral oxidation. Iron nanoparticles and purified by dialysis.

Benefits of technology

It realizes the simple and low-cost preparation of iron oxide nanoparticles with significant chiral optical signals in the aqueous phase. It is simple to operate and is suitable for subsequent large-scale production. It does not involve organic solvents, which improves biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191364A_ABST
    Figure CN119191364A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of chiral iron oxide nano-particles, and discloses a water-phase preparation method of chiral iron oxide nano-particles, which is simple and convenient to operate and can be used for preparing iron oxide nano-particles with remarkable chirality. The method comprises the following steps: step 10, dissolving FeCl3. 6H2O and FeCl2. 4H2O in ultrapure water to prepare a ferric salt precursor solution; step 20, a chiral ligand is dissolved in ultrapure water, the chiral ligand is tartaric acid, and a chiral ligand solution is prepared; step 30, adding the chiral ligand solution into a reaction container, and bubbling for the first time by using nitrogen; then adding the ferric salt precursor solution into a reaction container to form a first mixed solution, and carrying out second bubbling by using nitrogen; and adding stronger ammonia water into the reaction container to form a second mixed solution, continuously bubbling by using nitrogen in the reaction process, and reacting to prepare the chiral iron oxide nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing chiral iron oxide nanoparticles, and in particular to an aqueous phase preparation method for chiral iron oxide nanoparticles. Background Art

[0002] For molecules, spatial configuration is crucial. Chiral molecules exist in two forms, which are chemically identical but mirror images of each other, and are called enantiomers. Chirality is a universal property of matter. Chiral molecules are widely present in life systems and often exhibit a single chirality. For example, large molecules of DNA and RNA are right-handed structures; small molecules of amino acids, except for glycine, are left-handed structures. These chiral molecules play an important role in maintaining normal life activities. In a non-chiral environment, the physical and chemical properties of chiral molecules are basically the same; however, in a chiral environment, they can interact with other molecules in different ways. For example, although the physical and chemical properties of chiral drug molecules are basically the same, because the receptors or targets they act on are usually chiral biomacromolecules, enantiomeric drugs often show great differences in pharmacodynamics and pharmacokinetics in the body.

[0003] Existing studies have successfully introduced the physical property of chirality into inorganic nanostructures by directly using chiral ligands to induce in the synthesis, or by using chiral macromolecules as templates for self-assembly. Chiral nanostructures often have strong chiral optical activity and have shown great potential in optoelectronics, sensors, enantioselective catalysis, and chiral separation. Recent studies have found that nanoparticles with different chiral configurations can also cause differences in biological effects, which may be related to the stereospecificity and chiral selectivity exhibited by living systems in biochemical processes such as uptake, synthesis, and metabolism. The differences in biological effects caused by such chiral nanomaterials have brought new inspiration for the study of the biocompatibility and biotoxicity of nanomaterials and their applications in biomedical related fields.

[0004] Magnetic iron oxide nanoparticles can be prepared by aqueous coprecipitation, high temperature pyrolysis, solvothermal method and other methods. Among them, the iron oxide nanoparticles synthesized by aqueous coprecipitation method have many advantages, such as good biocompatibility, low price of raw material iron salt, mild reaction conditions, etc. Therefore, the iron oxide nanoparticles prepared by this method are often the first choice for biomedical research, and many applications have been developed, such as being used as an enhanced contrast agent for magnetic resonance imaging (MRI), a probe for cell labeling or a carrier material for drug delivery, and playing a role in magnetic hyperthermia therapy (MTT). In addition, research on its biological effects has also been widely carried out, such as exploring the effects of iron oxide nanoparticles on macrophage polarization and on the differentiation of bone marrow mesenchymal stem cells. In view of this, if chirality can be introduced into magnetic iron oxide nanoparticles and chiral iron oxide nanoparticles can be successfully prepared, it will provide an excellent platform for studying the interaction between chiral inorganic nanomaterials and life systems.

[0005] At present, research on the preparation of chiral iron oxide nanoparticles is very limited. The only reports in the literature include the use of ligand exchange method and self-assembly method. Among them, the chiral iron oxide nanoparticles obtained by the ligand exchange method involve the use of organic solvents in the preparation process, so that the prepared nanoparticles may lack biocompatibility; the self-assembly method requires the use of non-chiral ferroferric oxide nanoparticles as building blocks, penicillamine as a chiral ligand, and hydrophobic force-driven assembly to obtain chiral iron oxide superparticles. Its preparation process involves complex self-assembly, which is not conducive to large-scale, low-cost preparation. Therefore, how to achieve simple, low-cost and convenient subsequent amplification of chiral iron oxide nanoparticles in aqueous phase has become a major problem faced by technicians in this field. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an aqueous phase preparation method for chiral iron oxide nanoparticles which is completely different from the ligand exchange method and the self-assembly method, is easy to operate, and can prepare iron oxide nanoparticles with significant chirality.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The first object of the present invention is to provide an aqueous phase preparation method of chiral iron oxide nanoparticles, the method comprising:

[0009] Step 10, dissolving FeCl3·6H2O and FeCl2·4H2O in ultrapure water and uniformly mixing them to prepare an iron salt precursor solution;

[0010] Step 20, dissolving a chiral ligand in ultrapure water, wherein the chiral ligand is tartaric acid, and uniformly mixing the mixture to prepare a chiral ligand solution;

[0011] Step 30, adding the chiral ligand solution prepared in step 20 to a reaction container, and bubbling with nitrogen for the first time to remove all oxygen in the solution and the reaction container; then adding the iron salt precursor solution prepared in step 10 to the reaction container to form a first mixed solution, and bubbling with nitrogen for the second time to remove all oxygen in the first mixed solution and the reaction container; then adding concentrated ammonia water to the reaction container to form a second mixed solution, and continuously bubbling with nitrogen during the reaction process to react and produce chiral iron oxide nanoparticles.

[0012] Furthermore, in step 10, the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47-2.24:1.

[0013] Furthermore, in step 30, the time for the first bubbling and the second bubbling is 8 to 20 minutes respectively.

[0014] Furthermore, in step 30, in the second mixed solution, the molar ratio of the iron salt to the chiral ligand is 0.67 to 1:1.

[0015] Furthermore, in step 30, the pH of the second mixed solution is 8.27-9.71.

[0016] Furthermore, in step 30, the mass concentration of concentrated ammonia water is 25% to 28%. Furthermore, both step 10 and step 20 are performed at room temperature; in step 30, the reaction temperature is maintained at 30 to 90° C. and performed under nitrogen protection.

[0017] Furthermore, the step 30 further comprises, after the reaction of the second mixed solution is completed, the solution is cooled to room temperature and then dialyzed to obtain purified chiral iron oxide nanoparticles.

[0018] Furthermore, the molecular weight cut-off of the dialysis is not higher than 14000Da.

[0019] Furthermore, in step 30, the molar concentration of tartaric acid in the second mixed solution is 195-243 mM;

[0020] Furthermore, in the second mixed solution, the molar concentration of tartaric acid is 195 mM.

[0021] The second object of the present invention is to provide a chiral iron oxide nanoparticle, which is prepared by the above-mentioned preparation method.

[0022] The beneficial effects of the technical solution of the present invention are:

[0023] Compared with the prior art, the chiral iron oxide nanoparticles provided by the present invention are a new inorganic non-metallic biomaterial with chiral optical signals under visible light.

[0024] The present invention also provides a new preparation method, namely, an aqueous phase preparation method, which is different from the two chiral nanoparticle preparation methods of the prior art, namely, the ligand exchange method and the self-assembly method. According to the aqueous phase preparation method provided by the present invention, tartaric acid of a specific concentration is used as a chiral ligand, and chiral iron oxide nanoparticles having significant chiral optical signals in the visible light band can be prepared.

[0025] The present invention provides an aqueous phase preparation method for chiral iron oxide nanoparticles, which is simple to operate and convenient for subsequent scale-up, and can prepare chiral iron oxide nanoparticles with significant chirality. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) is a circular dichroism spectrum diagram of the samples of Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 1 (b) is a circular dichroism spectrum diagram of the samples of Example 1, Example 5 and Example 6 of the present invention; Figure 1 (c) is a circular dichroism spectrum diagram of the samples of Example 1, Example 7 and Example 8 of the present invention; Figure 1 (d) is the circular dichroism spectra of the samples of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0027] Figure 2 (a) is a UV-visible spectrogram of the samples of Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 2 (b) is a UV-Vis spectrogram of the samples of Example 1, Example 5 and Example 6 of the present invention; Figure 2 (c) is a UV-visible spectrogram of the samples of Example 1, Example 7 and Example 8 of the present invention; Figure 2 (d) is the UV-visible spectra of the samples of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0028] Figure 3 (a) is the asymmetry factor spectrum of the samples of Example 1, Example 2, Example 3 and Example 4 of the present invention; Figure 3 (b) is the asymmetry factor spectra of the samples of Examples 1, 5 and 6 of the present invention; Figure 3 (c) is the asymmetry factor spectra of the samples of Example 1, Example 7 and Example 8 of the present invention; Figure 3 (d) is the asymmetry factor spectrum of the samples of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0029] Figure 4(a) is a circular dichroism spectrum of L-tartaric acid (dextrorotatory tartaric acid) and D-tartaric acid (levorotatory tartaric acid) chiral molecules used in Example 1 of the present invention, Figure 4 (b) is the UV-visible absorption spectrum of the chiral molecules of L-tartaric acid and D-tartaric acid used in Example 1 of the present invention.

[0030] Figure 5 (a) is a circular dichroism spectrum of the samples prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5 of the present invention, Figure 5 (b) is a UV-visible absorption spectrum of the samples prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5 of the present invention, Figure 5 (c) is the asymmetry factor (g-factor) spectra of the samples prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5 of the present invention.

[0031] Figure 6 (a) is a circular dichroism spectrum of chiral iron oxide nanoparticles prepared by using L-tartaric acid and D-tartaric acid as chiral ligands according to the conditions in Example 1 of the present invention, Figure 6 (b) is a UV-visible absorption spectrum of chiral iron oxide nanoparticles prepared by using L-tartaric acid and D-tartaric acid as chiral ligands according to the conditions in Example 1 of the present invention, Figure 6 (c) is a graph showing the asymmetry factor (g-factor) of chiral iron oxide nanoparticles prepared by using L-tartaric acid and D-tartaric acid as chiral ligands under the conditions of Example 1.

[0032] Figure 7 (a) is a transmission electron microscope image of chiral iron oxide nanoparticles prepared by using L-tartaric acid as a chiral ligand in Example 1 of the present invention; Figure 7 (b) is a transmission electron microscope image of chiral iron oxide nanoparticles prepared by using D-tartaric acid as a chiral ligand in Example 1 of the present invention; Figure 7 (c) is the X-ray photoelectron spectrum of chiral iron oxide nanoparticles prepared in Example 1 of the present invention by using L-tartaric acid and D-tartaric acid as chiral ligands respectively; Figure 7 (d) is an X-ray powder diffraction pattern of chiral iron oxide nanoparticles prepared in Example 1 of the present invention by using L-tartaric acid and D-tartaric acid as chiral ligands respectively; Figure 7 (e) is the hysteresis loop diagram of chiral iron oxide nanoparticles prepared in Example 1 of the present invention by using L-tartaric acid and D-tartaric acid as chiral ligands respectively. DETAILED DESCRIPTION

[0033] The present invention is further explained below with reference to the examples, but the examples do not limit the present invention in any form.

[0034] An aqueous phase preparation method of chiral iron oxide nanoparticles according to an embodiment of the present invention comprises:

[0035] Step 10: Dissolve FeCl3·6H2O and FeCl2·4H2O in ultrapure water and mix them evenly to prepare an iron salt precursor solution.

[0036] In step 10, preferably, the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47-2.24:1. The chiral iron oxide nanoparticles prepared by this method are Fe3O4 nanoparticles. 3+ and Fe 2+ The molar ratio of Fe is 2:1, so the Fe 3+ and Fe 2+ The molar ratio of the iron salt precursor is controlled at about 2:1.

[0037] Step 20: dissolving a chiral ligand in ultrapure water, wherein the chiral ligand is tartaric acid (corresponding to English: Tartaric acid, abbreviated as: TA), and uniformly mixing the mixture to prepare a chiral ligand solution.

[0038] Among the chiral ligands, tartaric acid is selected in this embodiment. Among different chiral small molecules, including tartaric acid, aspartic acid, histidine, cysteine, lysine, threonine, arginine, glutamic acid, malic acid and N-acetylcysteine, only when tartaric acid is selected as the chiral ligand, the prepared iron oxide nanoparticles can show significant chiral optical signals in the visible light band.

[0039] Step 30, adding the chiral ligand solution prepared in step 20 to a reaction container, and using nitrogen to perform a first bubbling to remove all oxygen in the solution and the reaction container; then adding the iron salt precursor solution prepared in step 10 to the reaction container to form a first mixed solution, and using nitrogen to perform a second bubbling to remove all oxygen in the first mixed solution and the reaction container to prevent oxidation of divalent iron; then adding concentrated ammonia water to the reaction container to form a second mixed solution, so that trivalent iron and divalent iron are co-precipitated, and during the reaction process, nitrogen is continuously used for bubbling to finally generate chiral iron oxide nanoparticles.

[0040] In step 30, when adding iron salt precursor in tartaric acid solution (i.e. chiral ligand solution), coordination reaction of tartaric acid and iron salt precursor occurs. Strong ammonia is added in reaction vessel to form the second mixed solution, and the reaction occurring now is the coprecipitation reaction of ferric iron and ferrous iron, i.e. firstly generates ferric hydroxide and ferrous hydroxide, and after it reaches a certain degree of supersaturation, the two will gradually react to nucleate, and finally generate ferrosoferric oxide nanoparticles. In the formation process of chiral nanoparticles, chiral ligand can cause the lattice of nanoparticles to be distorted or deformed, thereby causing chirality, and then showing good chiral optical properties. No organic solvent is used in this aqueous phase preparation method.

[0041] As a preferred example, in step 30, the first bubbling time is 8 to 20 minutes. The second bubbling time is 8 to 20 minutes. By bubbling, the oxygen in the solution and the reaction container can be completely removed. Preferably, in step 30, the molar ratio of the iron salt to the chiral ligand in the second mixed solution is n(Fe 3+ +Fe 2+ ):n(TA)=0.67-1:1. More preferably, the molar ratio of the iron salt to the chiral ligand is n(Fe 3+ +Fe 2+ ):n(TA)=1:1. Iron salts include divalent iron and trivalent iron. The chiral properties of chiral nanoparticles are related to the amount of chiral ligand added during the preparation process. When the amount of chiral ligand added is small, the iron oxide nanoparticles obtained do not show significant chirality; as the amount of chiral ligand added increases, the iron oxide nanoparticles obtained show significant chirality and no longer change after reaching a certain concentration. When the molar ratio of iron salt to chiral ligand is in the range of 0.67 to 1:1, the iron oxide nanoparticles obtained have significant chirality.

[0042] As a preferred example, in step 30, the pH of the second mixed solution is 8.27-9.71. When the pH of the reaction solution is greater than 8, the proportion of ferrosoferric oxide nanoparticles in the product generated by the coprecipitation reaction of the iron salt precursor is relatively high.

[0043] As a preferred example, in step 30, the mass concentration of the concentrated ammonia water is 28%. Of course, other concentrations of concentrated ammonia water can also be selected.

[0044] As a preferred example, both step 10 and step 20 are carried out at room temperature. The room temperature is 18-22°C. In step 30, the reaction vessel is placed in a water bath at 30-90°C and carried out under nitrogen protection. The reaction vessel is placed in a water bath at 30-90°C, which can effectively control the temperature of the reaction solution. This temperature range can prepare chiral iron oxide nanoparticles with significant chirality. During the reaction, nitrogen is charged to remove oxygen from the reaction solution and the reaction vessel.

[0045] As a preferred example, step 30 further includes, after the reaction of the second mixed solution is completed, the solution is cooled to room temperature, and the reaction solution is dialyzed using a dialysis bag to obtain purified chiral iron oxide nanoparticles.

[0046] As a preferred example, in step 30, in the second mixed solution, the molar concentration of tartaric acid is 195-243 mM. When the molar concentration of tartaric acid is 195 mM, the corresponding n(Fe 3+ +Fe 2+ ):n(TA)=1:1, at this time, the chiral iron oxide nanoparticles prepared have significant chirality; when the molar concentration of tartaric acid is 243mM, the corresponding n(Fe 3+ +Fe 2+ ):n(TA)=0.67:1, the chiral optical properties of the prepared chiral iron oxide nanoparticles are not further improved compared to when the tartaric acid concentration is 195mM. More preferably, the molar concentration of tartaric acid is 195mM.

[0047] The method of the present application uses a chiral ligand as an inducer to prepare chiral iron oxide nanoparticles with good monodispersity and easy to prepare repeatedly. The method scheme of the present application is simple and easy to implement, and the whole process is carried out in an aqueous phase and does not involve complicated operating conditions. Therefore, if the method of the present invention is scaled up from laboratory scale to pilot scale, the difficulties faced are expected to be much smaller than those of chiral iron oxide nanoparticles prepared by ligand exchange method and self-assembly method.

[0048] The following examples and comparative examples are used to illustrate that the method of the present application has good technical performance.

[0049] Example 1

[0050] A method for preparing chiral iron oxide nanoparticles, comprising:

[0051] Step 10: Dissolve 600 mg FeCl3·6H2O (2.22 mmol) and 300 mg FeCl2·4H2O (1.51 mmol) in 5 mL ultrapure water and mix them evenly to prepare an iron salt precursor solution; the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47:1.

[0052] Step 20, dissolving 3.73 mmol of a chiral ligand in 10 mL of ultrapure water, wherein the chiral ligand is L-tartaric acid (dextrorotatory tartaric acid), and uniformly mixing to prepare a chiral ligand solution;

[0053] Step 30, place the reaction container in a 60°C water bath. Add the chiral ligand solution to the reaction container, and use nitrogen for the first bubbling for 10 minutes to remove all oxygen in the solution and the reaction container; then add the iron salt precursor solution to the reaction container to form a first mixed solution, and use nitrogen for a second bubbling for 10 minutes to remove all oxygen in the first mixed solution and the reaction container; then add 4 mL of concentrated ammonia water with a mass concentration of 28% to the reaction container to form a second mixed solution, and continue to use nitrogen for bubbling during the reaction. After the reaction is completed, wait for the solution to cool to room temperature, and use a 14000Da dialysis bag to dialyze the reaction solution to remove unreacted substances in the solution to prepare chiral iron oxide nanoparticles. In the second mixed solution, the molar ratio of iron salt to chiral ligand is n(Fe 3+ +Fe 2+ ):n(TA)=1:1; the molar concentration of tartaric acid is 195 mM. The pH of the second mixed solution is 9.71.

[0054] Example 2

[0055] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 10, 698.0 mg FeCl3·6H2O (2.58 mmol) and 228.2 mg FeCl2·4H2O (1.15 mmol) are dissolved in 5 mL ultrapure water and uniformly mixed to prepare an iron salt precursor solution; the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 2.24:1.

[0056] Example 3

[0057] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 10, 672.1 mg FeCl3·6H2O (2.49 mmol) and 247.2 mg FeCl2·4H2O (1.24 mmol) are dissolved in 5 mL ultrapure water and uniformly mixed to prepare an iron salt precursor solution; the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 2:1.

[0058] Example 4

[0059] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 10, 630.6 mg FeCl3·6H2O (2.33 mmol) and 277.7 mg FeCl2·4H2O (1.40 mmol) are dissolved in 5 mL ultrapure water and uniformly mixed to prepare an iron salt precursor solution; the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.67:1.

[0060] Example 5

[0061] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 30, 1 mL of concentrated ammonia water with a mass concentration of 28% is added to the reaction container so that the pH of the second reaction solution is 8.27.

[0062] Example 6

[0063] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 30, 2 mL of concentrated ammonia water with a mass concentration of 28% is added to the reaction container so that the pH of the second reaction solution is 9.42.

[0064] Example 7

[0065] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 30, the reaction container is placed in a 30° C. water bath.

[0066] Example 8

[0067] A method for preparing chiral iron oxide nanoparticles is the same as the method for preparing chiral iron oxide nanoparticles in Example 1, except that in step 30, the reaction container is placed in a 90° C. water bath.

[0068] Example 9

[0069] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 20, the amount of chiral ligand used is 5.60 mmol, so that in the second mixed solution of step 30, the molar concentration of L-tartaric acid is 243 mM, and the molar ratio of iron salt to chiral ligand is 0.67:1.

[0070] Comparative Example 1

[0071] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 20, the chiral ligand is L-aspartic acid (dextrorotatory aspartic acid).

[0072] Comparative Example 2

[0073] A method for preparing chiral iron oxide nanoparticles is the same as the method for preparing chiral iron oxide nanoparticles in Example 1, except that in step 20, the chiral ligand is L-cysteine ​​(D-cysteine).

[0074] Comparative Example 3

[0075] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 20, the amount of chiral ligand used is 1.87 mmol, so that in the second mixed solution of step 30, the molar concentration of L-tartaric acid is 97 mM, and the molar ratio of iron salt to chiral ligand is 2:1.

[0076] Comparative Example 4

[0077] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 20, the amount of chiral ligand used is 0.37 mmol, so that in the second mixed solution of step 30, the molar concentration of L-tartaric acid is 19 mM, and the molar ratio of iron salt to chiral ligand is 10:1.

[0078] Comparative Example 5

[0079] A method for preparing chiral iron oxide nanoparticles is the same as the preparation method of Example 1, except that in step 20, the amount of chiral ligand used is 0.19 mmol, so that in the second mixed solution of step 30, the molar concentration of L-tartaric acid is 10 mM, and the molar ratio of iron salt to chiral ligand is 20:1.

[0080] Test 1: Chiral optical performance test

[0081] Test method: Place the sample in a quartz cuvette and use a JACSO J-1500 circular dichroism spectrometer to measure the circular dichroism spectrum and UV-visible absorption spectrum of the sample at room temperature 20°C. Using a circular dichroism spectrometer to test chiral optical signals is the most convenient test method to measure the chirality of a substance. Chiral iron oxide nanoparticles have good chiral optical properties, which is a manifestation of their significant chirality.

[0082] The chiral iron oxide nanoparticles prepared in Examples 1 to 8, Comparative Example 1, and Comparative Example 2 were respectively used as samples and tested according to the above method. The results are as follows: Figure 1 and Figure 2 shown.

[0083] Figure 1 (a) is the circular dichroism spectra of the samples of Example 1, Example 2, Example 3 and Example 4, Figure 1 (b) is the circular dichroism spectra of the samples of Example 1, Example 5 and Example 6, Figure 1 (c) is the circular dichroism spectra of the samples of Example 1, Example 7 and Example 8, Figure 1 (d) is the circular dichroism spectra of the samples of Example 1, Comparative Example 1 and Comparative Example 2. In the figure, L-tartaric acid represents dextrorotatory tartaric acid.

[0084] Depend on Figure 1(a) It can be seen that when the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47:1, the chiral iron oxide nanoparticles prepared show stronger chiral optical signals in the 350-400nm band. Figure 1 (b) It can be seen that under different pH conditions, the chiral optical signals of the obtained chiral iron oxide nanoparticles are not much different. Figure 1 (c) It can be seen that when the reaction temperature is 60°C, the chiral iron oxide nanoparticles obtained show stronger chiral optical signals in the visible light band of 350-400nm; Figure 1 (d) It can be seen that only when tartaric acid is used as the chiral ligand, the obtained chiral iron oxide nanoparticles show obvious chiral optical signals in the 350-400nm band. When aspartic acid is used as the chiral ligand, the obtained iron oxide nanoparticles do not show obvious chiral optical signals. When cysteine ​​is used as the chiral ligand, the obtained chiral iron oxide nanoparticles only show obvious chiral optical signals in the ultraviolet band of 250-300nm.

[0085] Figure 2 (a) is the UV-visible absorption spectra of the samples of Example 1, Example 2, Example 3 and Example 4, Figure 2 (b) is the UV-visible absorption spectra of the samples of Example 1, Example 5 and Example 6, Figure 2 (c) is the UV-visible absorption spectra of the samples of Example 1, Example 7 and Example 8, Figure 2 (d) is the UV-visible absorption spectra of the samples of Example 1, Comparative Example 1 and Comparative Example 2. In the figure, L-tartaric acid represents dextrorotatory tartaric acid.

[0086] Depend on Figure 2 (a) It can be seen that: at different molar ratios of FeCl3·6H2O and FeCl2·4H2O, the UV-visible absorption spectra of the chiral iron oxide nanoparticles prepared are not much different; Figure 2 (b) It can be seen that: under different pH conditions, the UV-visible absorption spectra of the prepared chiral iron oxide nanoparticles are not much different; Figure 2 (c) It can be seen that: under different reaction temperature conditions, the UV-visible absorption spectra of the chiral iron oxide nanoparticles prepared are not much different; Figure 2 (d) It can be seen that the UV-visible absorption spectra of iron oxide nanoparticles synthesized using L-aspartic acid and L-cysteine ​​as chiral ligands are relatively similar, with an obvious shoulder peak at 400nm. The iron oxide nanoparticles synthesized using L-tartaric acid as a chiral ligand do not have an obvious characteristic peak in the range of 250-650nm.

[0087] Test 2: Calculate the asymmetry factor (g-factor)

[0088] The calculation formula of the asymmetry factor is: g = CD / (32980 x Abs), where g represents the asymmetry factor, CD represents the value of the ellipticity in the circular dichroism spectrum in a specific spectral band, the unit is mDeg, and Abs represents the value of the absorption value in the ultraviolet-visible absorption spectrum in a specific spectral band, the unit is au.

[0089] The asymmetry factor eliminates the effect of the concentration of the chiral ligand solution on the chiral optical properties and is usually used to compare the strength of the chiral optical signals between different substances.

[0090] For the samples prepared in Examples 1 to 8, Comparative Example 1 and Comparative Example 2, their asymmetry factors were calculated respectively.

[0091] Figure 3 (a) is the asymmetry factor spectrum of the samples of Example 1, Example 2, Example 3 and Example 4, Figure 3 (b) is the asymmetry factor spectrum of the samples of Example 1, Example 5 and Example 6, Figure 3 (c) is the asymmetry factor spectrum of the samples of Example 1, Example 7 and Example 8, Figure 3 (d) is the asymmetry factor spectrum of the samples of Example 1, Comparative Example 1 and Comparative Example 2. Among them, the maximum absolute value of the asymmetry factor of the sample prepared in Example 1 is about 1.9×10 -4 The maximum absolute value of the asymmetry factor of the sample prepared in Example 2 is about 8.1×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Example 3 is about 1.2×10 -4 The maximum absolute value of the asymmetry factor of the sample prepared in Example 4 is about 1.1×10 -4 The maximum absolute value of the asymmetry factor of the sample prepared in Example 5 is about 8.5×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Example 6 is about 9.0×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Example 7 is about 8.7×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Example 8 is about 8.0×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 1 is about 7.0×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 2 is about 1.5×10 -4 .

[0092] By comparison Figure 3The data in (a) show that when the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47:1, the maximum absolute value of the asymmetry factor of the chiral iron oxide nanoparticles is larger, indicating that it has stronger chirality. Figure 3 From the data in (b), we can see that when the pH is 9.71, the maximum absolute value of the asymmetric factor of the chiral iron oxide nanoparticles is larger, indicating that it has strong chirality. Figure 3 From the data in (c), we can see that when the reaction temperature is 60°C, the maximum absolute value of the asymmetric factor of the chiral iron oxide nanoparticles is larger, indicating that it has stronger chirality. Figure 3 The data in (d) show that when tartaric acid is used as the chiral ligand, the maximum absolute value of the asymmetry factor of the chiral iron oxide nanoparticles prepared is larger, indicating that it has a stronger chirality. The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 2 appears in the range of 250-300nm, while the maximum absolute value of the asymmetry factor of the sample prepared in Example 1 appears in the range of 350-400nm.

[0093] Test 3:

[0094] In order to prove that the chiral signal of the chiral iron oxide nanoparticles is not derived from the free chiral molecules therein, the chiral optical properties of the chiral molecules used in the sample of Example 1 were tested by circular dichroism spectroscopy using the method of Test 1. The results are as follows: Figure 4 The chiral ligands in Example 1 are L-tartaric acid (dextrorotatory tartaric acid) and D-tartaric acid (levorotatory tartaric acid).

[0095] Figure 4 (a) is the circular dichroism spectrum of L-tartaric acid and D-tartaric acid. Figure 4 (b) is the UV-visible absorption spectrum of L-tartaric acid and D-tartaric acid. Figure 4 (a) It can be seen that in the range of 300-450nm, chiral molecules do not show obvious chiral signals. Figure 4 (b) It can be seen that L-tartaric acid and D-tartaric acid do not have obvious characteristic peaks in the range of 280-650nm, and their UV-visible absorption is almost zero.

[0096] Therefore, the chiral signal of chiral iron oxide nanoparticles does not come from the free chiral molecules therein.

[0097] Test 4:

[0098] The chiral optical performance test method of Test 1 was used to test the chiral optical performance of the samples prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5, and the asymmetry factors of the samples prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were calculated using the method of Test 2. The results are as follows: Figure 5 shown. Figure 5 (a) is a circular dichroism spectrum of each sample prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5, Figure 5 (b) is a UV-visible absorption spectrum of each sample prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5, Figure 5 (c) is the asymmetry factor spectrum of each sample prepared in Example 1, Example 9, Comparative Example 3, Comparative Example 4 and Comparative Example 5.

[0099] Depend on Figure 5 (a) It can be seen that when the concentration of tartaric acid in the second mixed solution is 10mM, 19mM and 97mM, the chiral iron oxide nanoparticles obtained do not show obvious chiral optical signals in the 350-400nm band; when the concentration of tartaric acid in the second mixed solution is 195mM and 243mM, the chiral iron oxide nanoparticles obtained show relatively obvious chiral optical signals in the 350-400nm band. Figure 5 (b) It can be seen that when the concentration of tartaric acid in the second mixed solution is in the range of 10-243 mM, the UV-visible absorption spectra of the chiral iron oxide nanoparticles obtained are not much different. Figure 5 (c) It can be seen that the maximum absolute value of the asymmetry factor of the sample prepared in Example 1 is about 1.9×10 -4 The maximum absolute value of the asymmetry factor of the sample prepared in Example 9 is about 1.9×10 -4 The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 3 is about 8.0×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 4 is about 5.5×10 -5 The maximum absolute value of the asymmetry factor of the sample prepared in Comparative Example 5 is about 6.2×10 -5 . It can be seen that the concentration of tartaric acid added to the reaction system significantly affects the chiral optical properties of chiral iron oxide nanoparticles. As the concentration of tartaric acid in the reaction system increases, the chiral optical signal of the iron oxide nanoparticles gradually increases until the concentration of tartaric acid in the system increases to 195mM, reaching the strongest chiral optical signal and showing the maximum value of the absolute value of the highest asymmetry factor. After that, the chiral optical signal of the iron oxide nanoparticles no longer changes with the increase of tartaric acid concentration.

[0100] The chiral iron oxide nanoparticles prepared in Example 1 have a stronger chirality than all the examples and comparative examples. Referring to the conditions in Example 1, L-tartaric acid and D-tartaric acid were used as chiral ligands to prepare chiral iron oxide nanoparticles. According to the methods of Test 1 and Test 2 above, circular dichroism spectra, UV-visible absorption spectra and asymmetry factor (g-factor) spectra were obtained for the prepared chiral iron oxide nanoparticles, as shown in FIG. Figure 6 As shown. Among them, Figure 6 (a) is the circular dichroism spectrum of the sample prepared by using L-tartaric acid and D-tartaric acid as chiral ligands respectively with reference to the conditions in Example 1, Figure 6 (b) is the UV-visible absorption spectrum of the samples prepared by using L-tartaric acid and D-tartaric acid as chiral ligands respectively under the conditions in Example 1, Figure 6 (c) is the asymmetry factor (g-factor) spectrum of the samples prepared by using L-tartaric acid and D-tartaric acid as chiral ligands respectively under the conditions of Example 1.

[0101] from Figure 6 It can be seen that the chiral iron oxide nanoparticles prepared by using L-tartaric acid and D-tartaric acid as chiral ligands respectively have good symmetry in their circular dichroism spectra and asymmetry factor (g-factor) spectra, and their UV-visible absorption spectra are not much different and are almost exactly the same.

[0102] Test 5:

[0103] The chiral iron oxide nanoparticles prepared in Example 1 were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction phase analysis (XRD) and vibrating sample magnetometer (VSM), including the characterization of the chiral iron oxide nanoparticles prepared by the method of Example 1, using D-tartaric acid instead of L-tartaric acid as the chiral ligand.

[0104] Transmission Electron Microscope A transmission electron microscope of model Titan G2 produced by Thermo Fisher Scientific, USA, was used to photograph the iron oxide nanoparticles prepared in Example 1 at an operating voltage of 300 kV.

[0105] Figure 7(a) is a transmission electron microscope image of iron oxide nanoparticles prepared using L-tartaric acid in Example 1, Figure 7 (b) is a transmission electron microscope image of iron oxide nanoparticles prepared using D-tartaric acid in Example 1. Figure 7 (a) and Figure 7 (b) It can be seen that the particle size of the prepared chiral iron oxide nanoparticles is about 2 nm.

[0106] The sample prepared in Example 1 was tested by X-ray photoelectron spectroscopy using an X-ray photoelectron spectrometer, model Thermo escalab 250XI, produced by Thermo Fisher Scientific, USA. The results are as follows: Figure 7 (c). Figure 7 (c) It can be seen that the chiral iron oxide nanoparticles contain Fe, O, and C elements.

[0107] The sample prepared in Example 1 was tested using an X-ray powder diffractometer, model Bruker D8-Discover, produced by Bruker, Germany. The results are as follows: Figure 7 (d). Figure 7 (d) It can be seen that the chiral iron oxide nanoparticles have no obvious crystal diffraction peaks due to their small particle size.

[0108] The samples prepared in Example 1 were tested using a vibrating sample magnetometer model Lake Shore 7407 produced by Lake Shore Company of the United States. The results are as follows: Figure 7 (e) is shown. Figure 7 (e) It can be seen that chiral iron oxide nanoparticles have weak paramagnetism.

[0109] The Zeta potential of the sample prepared in Example 1 was tested using a dynamic light scattering instrument, model Zetasizer Pro, produced by Malvern, UK. The test results show that the Zeta potential of the chiral iron oxide nanoparticles prepared in Example 1 using L-tartaric acid and D-tartaric acid as chiral ligands was about -30 mV.

[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing chiral iron oxide nanoparticles in aqueous phase, characterized in that: The method comprises: Step 10, dissolving FeCl3·6H2O and FeCl2·4H2O in ultrapure water and uniformly mixing them to prepare an iron salt precursor solution; Step 20, dissolving a chiral ligand in ultrapure water, wherein the chiral ligand is tartaric acid, and uniformly mixing the mixture to prepare a chiral ligand solution; Step 30, adding the chiral ligand solution prepared in step 20 to a reaction container, and bubbling with nitrogen for the first time to remove all oxygen in the solution and the reaction container; then adding the iron salt precursor solution prepared in step 10 to the reaction container to form a first mixed solution, and bubbling with nitrogen for the second time to remove all oxygen in the first mixed solution and the reaction container; then adding concentrated ammonia water to the reaction container to form a second mixed solution, and continuously bubbling with nitrogen during the reaction process to react and produce chiral iron oxide nanoparticles.

2. The method according to claim 1, characterized in that In the step 10, the molar ratio of FeCl3·6H2O to FeCl2·4H2O is 1.47-2.24:

1.

3. The method according to claim 1, characterized in that In step 30, the time for the first bubbling and the second bubbling is 8 to 20 minutes respectively.

4. The method according to claim 1, characterized in that: In the step 30, in the second mixed solution, the molar ratio of the iron salt to the chiral ligand is 0.67 to 1:

1.

5. The method according to claim 1, characterized in that In step 30, the pH of the second mixed solution is 8.27-9.

71.

6. The method according to claim 1, characterized in that The steps 10 and 20 are both carried out at room temperature; the step 30 is carried out under nitrogen protection while maintaining the reaction temperature at 30-90°C.

7. The method according to claim 1, characterized in that The step 30 also includes, after the reaction of the second mixed solution is completed, the solution is cooled to room temperature and then dialyzed to obtain purified chiral iron oxide nanoparticles.

8. The method according to claim 7, characterized in that The molecular weight cut-off for dialysis is no higher than 14000Da.

9. The method according to claim 1, characterized in that: In step 30, the molar concentration of tartaric acid in the second mixed solution is 195-243 mM; preferably, the molar concentration of tartaric acid in the second mixed solution is 195 mM.

10. A chiral iron oxide nanoparticle, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 9.